Increased Intensity of Student Loyalty based on Quality of Service, Satisfaction and Confidence - Asriatuzzeky Asriatuzzeky; Naila Hayati; Wahyuli Lius Zen; Rehani Rehani; Zulvia Trinova (Budapest International Research and Critics University, 2022)
Student loyalty indicates a quality college. Good service quality is the ability of the institution to provide service according to customer requests, listen to all forms of customer complaints, and provide a positive reaction to customer complaints so as not to cause an unfavorable perception of the quality of the services provided. The quality of service at an institution greatly affects customer satisfaction. customer satisfaction with an institution needs to be maintained. Satisfaction has an influence on trust. Through the trust of students who are studying, they will be loyal to complete their education in the high education.